Restoring Parents’ Role: Tongkonan-Based Education in Toraja Christian Families - Rante Salu, Syani Bombongan; Herman, Joffri; Silaban, Tri Oktavia Hartati (Sekolah Tinggi Teologi Simpson Ungaran, 2025)
Education is very important for the progress of a region and a nation. In Indonesia, particularly in Tana Toraja, education is still a trending topic, so the government has made it one of its main programs, marked by the construction of schools, facilities that are starting to improve, and educators who are becoming more skilled with more advanced and contextual educational concepts. However, this situation seems to justify parents' decision to entrust the entire responsibility of education to schools. The purpose of this study is to restore the primary role of Christian educators, namely parents, by analyzing the concept of education in the Tongkonan culture. This study was conducted using qualitative research with descriptive analysis of findings through literature review and interviews. The results of the study indicate that the concept of education in Tongkonan, based on the independent curriculum, can restore the natural role of educators in Christian families in Toraja. Parents act as teachers, communicators of norms, teachers of life values, and teachers of symbolic meanings, which are then elaborated in principles, processes, and practices in teaching.